Drug change: 'a hassle like no other'. An in-depth investigation using the Danish patient safety database and focus group interviews with Danish hospital personnel - Joo Hanne Poulsen; Rikke Mie Rishøj; Hanne Fischer; Trine Kart; Lotte Stig Nørgaard; Christian Sevel; Peter Dieckmann; Marianne Hald Clemmensen (SAGE Publishing, 2019)
Background: Drug change (DC) is a common challenge in Danish hospitals. It affects the work of hospital personnel and has potentially serious patient safety consequences. Focus on medication safety is becoming increasingly important in the prevention of adverse events. The aim of this study is to identify and describe patient safety challenges related to DCs, and to explore potential facilitators to improve patient safety in the medication process in Danish hospital setting. Method: Two qualitative methods were combined. Data were obtained from the Danish Patient Safety Database (DPSD) containing incidents reports of adverse events related to DCs. Additionally, five semi-structured focus group interviews with hospital personnel (doctors, nurses, pharmacists and pharmacy technicians) from the five regions of Denmark were held. Results: The DPSD search identified 88 incidents related to DCs due to tender or drug shortage. The incidents were linked to prescribing errors, incorrect dose being dispensed/administered, and delayed/omitted treatment. Four themes from the interviews emerged: (1) challenges related to the drug itself; (2) situational challenges; (3) challenges related to the organization/IT systems/personnel; (4) facilitators/measures to ensure patient safety. Conclusion: DC is as a complex challenge, especially related to drug shortage. The results allow for a deeper understanding of the challenges and possible facilitators of DCs on the individual and organizational level. Pharmacy personnel were identified to play a key role in ensuring patient safety of DCs in hospitals. Indeed, this emphasizes that pharmacy personnel should be engaged in developing patient safety strategies and support hospital personnel around drug changes.